IMPLEMENTATION OF THE ROLE PLAYING METHOD IN DEVELOPING ASPECTS OF EARLY CHILDHOOD SOCIAL DEVELOPMENT AT RA RAUDHLATUL HIDAYAH CIREBON - Husnul Hafidhoh (International Conference on Economic Business and Social Science, 2023)
This research article aims to find out how to implement the role playing method in developing aspects of early childhood development in learning. The method used by tutors greatly affects the growth of children. Various types of methods that can be used for early childhood development include the role playing method. The current phenomenon is that children's social potential is not increasing very much, in this case it occurs because of environmental aspects and a lack of activities that can increase children's social potential, causing some children to be unable to interact and have a good social conscience, for example, not wanting to work with friends their own age. The method used in this research is descriptive qualitative method. Especially the social development of children. In the topic role-playing method that can be given describes topics that are close to the child's world, for example: family and professions with these topics, role-playing will take place more effectively because children know and act directly on the characters they will play and children will interact with other friends . So that in this way social development can be honed to the maximum